Cohorting KPC+ Klebsiella pneumoniae (KPC-Kp)–Positive Patients—A Genomic Exposé of Cross-Colonization Hazards. (October 2020) - Hawken, Shawn; Hayden, Mary; Lolans, Karen; Yelin, Rachel; Weinstein, Robert; Lin, Michael; Snitkin, Evan
Abstract : Background: Long-term acute-care hospitals (LTACHs) are disproportionately burdened by multidrug-resistant organisms (MDROs) like KPC-Kp. Although cohorting KPC-Kp+ patients into rooms with other carriers can be an outbreak-control strategy and may protect negative patients from colonization, it is unclear whether cohorted patients are at unintended increased risk of cross colonization with additional KPC-Kp strains. Methods: Cohorting KPC-Kp+ patients at admission into rooms with other positive patients was part of a bundled intervention that reduced transmission in a high-prevalence LTACH. Rectal surveillance culturing for KPC-Kp was performed at the start of the study, upon admission, and biweekly thereafter, capturing 94% of patients. We evaluated whole-genome sequencing (WGS) evidence of acquisition of distinct KPC-Kp strains in a convenience sample of patients positive for KPC-Kp at study start or admission to identify plausible secondary KPC-Kp acquisitions. Results: WGS multilocus sequence type (MLST) strain variability was observed among the 452 isolates from the 254 patients colonized by KPC-Kp (Fig. 1). Among the 32 patients who were positive at the beginning of the study or admission and had a secondary isolate collected at a later date (median, 89 days apart, range, 2–310 days), 17 (53%) had secondary isolates differing by MLST from their admission isolate. Although 60% of the KPC-Kp in the study was ST258, there was substantial genomic variation within ST258 isolates from the same patient (range, 0–102 genetic variants), suggesting multiple acquisitions of distinct ST258 isolates. Among the 17 patients who imported ST258 and had ST258 isolated again later, 11 (65%) carried secondary isolates genetically closer to isolates from other importing patients than to their own ST258 (Fig. 2). Examination of spatiotemporal exposures among patients with evidence of multiple acquisitions revealed that 11 (65%) patients with multiple MLSTs shared a room with a patient who was colonized with an isolate matching the secondary MLST, and 6 (35%) patients who carried multiple distinct ST258 isolates shared a room with a patient who imported these closely related isolates prior to secondary acquisition. Conclusions: Half of patients who imported KPC-Kp and had multiple isolates available had genomically supported secondary acquisitions linked to roommates who carried the acquired strains. Although cohorting is intended to protect negative patients from acquiring MDROs, this practice may promote multiple strain acquisitions by colonized patients in the cohort, potentially prolonging the period of MDRO carriage and increasing time at risk of infection. Our findings add to the debate about single-patient rooms, which may be preferred to cohorts to minimize potential harms by reducing MDRO transmission. Funding: None Disclosures: None